Gait Asymmetry Variation in Kinematics, Kinetics, and Muscle Force along with the Severity Levels of Knee Osteoarthritis - Junqing Wang; Qinsheng Hu; Chenyu Wu; Shiqi Li; Qian Deng; Ruoliang Tang; Kang Li; Yong Nie; Bin Shen (Orthopaedic Surgery, 2023)
Objective Knee osteoarthritis (OA) patients exhibit greater gait asymmetry than healthy controls. However, gait asymmetry in kinematics, kinetics and muscle forces across patients with different severity levels of knee OA is still unknown. The study aimed to investigate the changes of gait asymmetry in lower limb kinematics, kinetics, and muscle force across patients with different severity levels of knee OA. Methods This is a cross‐sectional study. From January 2020 to January 2021, 118 patients with symptomatic and radiographic medial knee OA were categorized into three groups using the Kellgren and Lawrence scale (mild: grade 1 and 2, n = 37; moderate: grade 3, n = 31; severe: grade 4, n = 50). During self‐paced walking, marker trajectories and ground reaction forces data were recorded. Musculoskeletal simulations were used to determine gait kinematics, kinetics, and muscle force. One‐way analysis of variance with Tukey's post‐hoc test was used to evaluate group difference. Paired‐sample t‐test was used to compared the between‐limb difference. Results In the Severe group, significantly greater asymmetry index in knee flexion/extension range of motion (45%) was observed with a greater value on the contralateral side (p < 0.01), compared to the Mild (15%) and Moderate (15%) groups. Significantly higher peak hip contact force (JCF) on the contralateral side was found in the Mild (more affected side: 3.80 ± 0.67 BW, contralateral side: 4.01 ± 0.58 BW), Moderate (more affected side: 3.67 ± 0.56 BW, contralateral side: 4.07 ± 0.81 BW), and Severe groups (more affected side: 3.66 ± 0.79 BW, contralateral side: 3.94 ± 0.64 BW) (p < 0.05). Significantly greater gluteus medius muscle force on the contralateral side was found in Mild (more affected side: 0.48 ± 0.09 BW, contralateral side: 0.52 ± 0.12 BW), Moderate (more affected side: 0.45 ± 0.10 BW, contralateral side: 0.51 ± 0.15 BW), and Severe groups (more affected side: 0.42 ± 0.15 BW, contralateral side: 0.47 ± 0.12 BW) (p < 0.05). The contralateral side showing significantly higher peak knee adduction moment and medial knee JCF was only observed in the Mild group (p < 0.05). Conclusions Gait asymmetry in kinematics and muscle forces increased from mild to severe knee OA. Asymmetrical gait pattern tends to transfer loads from the more affected side to the contralateral side. Peak hip JCF and gluteus medius muscle force can be used to detect this asymmetrical gait pattern in patients with knee OA, regardless of severity levels.